Participación de la mujer en las decisiones sobre el uso y la intensidad de siembra de variedades de arroz en ecuador - Marín Salazar, Diego (2018)
Women’s contribution in agriculture is often not recognized, and this limits thedesign of policies for targeting gender equality. The most recent body of literaturehas provided lessons about the role of women and its importance to improveagricultural productivity. However, these studies show that women’s contributionin agriculture is heterogeneous and context specific. Furthermore, there is a lackof evidence in Latin America about women’s roles and even less for specific cropslike rice in Ecuador, which is considered to be a male-dominated crop. Our studyconfirms previous qualitative study results that demonstrate the importance ofwomen in rice production. Households, where women participate in the decisionprocess to select rice varieties, are more likely to adopt modern varieties. In addition,in households that adopt improved varieties, women’s participation in the decisionabout which variety to plant, is correlated with a larger land area sown in thosevarieties than in households without female participation. These conclusions cansupport the dialogue and design of policies that aim to improve the rice sector andincrease gender equality